2019
DOI: 10.13057/asianjfor/r030102
|View full text |Cite
|
Sign up to set email alerts
|

Tree species diversity and structural composition: The case of Durgapur Hill Forest, Netrokona, Bangladesh

Abstract: Abstract. Rahman MdR, Rahman MdM, Chowdhury MdA, Akhter J. 2019. Tree species diversity and structural composition: The case of Durgapur Hill Forest, Netrokona, Bangladesh. Asian J For 3: 10-19. Tree species diversity and stand structure of Durgapur hill forest were assessed through stratified random sampling method using sample plots of 20 m x 20 m in size during the period of October 2017 to May 2018. A total of 1436 stems of ≥5 cm DBH of 56 tree species belonging to 50 genera and 29 families were enumerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Overall, the two AAC presents a diversified and equitable specific richness. Our results converge with the works of [64] which stipulate that when the equitability is high, the dispersion of the elements of biodiversity would be equitable. Finally, the correlation between the age of the road and the indices of diversity showed that there is no link between the ages of secondary roads post-logging and the indices of diversity (p-value > 0.005).…”
Section: The Specific Richness and The Intra And Inter Annual Allowab...supporting
confidence: 89%
“…Overall, the two AAC presents a diversified and equitable specific richness. Our results converge with the works of [64] which stipulate that when the equitability is high, the dispersion of the elements of biodiversity would be equitable. Finally, the correlation between the age of the road and the indices of diversity showed that there is no link between the ages of secondary roads post-logging and the indices of diversity (p-value > 0.005).…”
Section: The Specific Richness and The Intra And Inter Annual Allowab...supporting
confidence: 89%
“…In CWS, the number of naturally regenerating species (105) and family (35) was higher than that of similar natural forests of Bangladesh. Rahman et al (2019) enumerated 56 naturally regenerating species from Durgapur hill forest. Hossain et al (2004) reported 64 naturally regenerating tree species from natural forests of Chittagong (South) Forest Division.…”
Section: Biological Diversity Indices Of Regeneration Speciesmentioning
confidence: 99%
“…Durgapur hill forest is one of the remnant places of Sal forest patches in Bangladesh where economically and ecologically valuable tree species are needs to be prioritized for conservation and scientific management (Rahman, Rahman, Chowdhury, & Akhter, 2019). The forest has been cleared brutally within the last 30 to 50 years as the demand for energy, construction, wood, food, fodder has increased as a result of the increase in both human and livestock.…”
Section: Introductionmentioning
confidence: 99%
“…The main causes of deforestation and forest degradation in this area were tree cutting for fuelwood, and construction materials production for sale especially. A number of studies are available focused on natural regeneration status in different natural forests of Bangladesh provide potential information for many native tree species (Haider et al, 2017;Hossain, Hossain, Salam, & Rahman, 2013;Hossain, Azad, & Alam, 1999;Hossain & Hossain, 2014;Motaleb & Hossain, 2007;Miah, Udin, & Bhuiyan, 1999;Nur, Nandi, Jashimuddin, & Hossain, 2016;Rahman, Rahman, Chowdhury, & Akhter, 2019;Rahman et al, 2011) and diversity in forest (Chowdhury, Islam, Hafiz, & Islam, 2018;Rahman et al, 2019), but research work on regeneration aspect of forest is not available where Durgapur hill forest lacks information regarding natural regeneration, stocking, and conservation issues. This study will enrich the knowledge of natural regeneration and quantitative distribution of plant species in the case of hill forest which may be useful in providing guidelines for future management of forest.…”
Section: Introductionmentioning
confidence: 99%